2016
DOI: 10.1002/anie.201603970
|View full text |Cite
|
Sign up to set email alerts
|

A Dinitrogen Dicopper(I) Complex via a Mixed‐Valence Dicopper Hydride

Abstract: Low-temperature reaction of the tris(pyrazolyl)borate copper(II) hydroxide [(iPr2) TpCu]2 (μ-OH)2 with triphenylsilane under a dinitrogen atmosphere gives the bridging dinitrogen complex [(iPr2) TpCu]2 (μ-1,2-N2 ) (3). X-ray crystallography reveals an only slightly activated N2 ligand (N-N: 1.111(6) Å) that bridges between two monovalent (iPr2) TpCu fragments. While DFT studies of mono- and dinuclear copper dinitrogen complexes suggest weak π-backbonding between the d(10) Cu(I) centers and the N2 ligand, they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 73 publications
2
39
0
Order By: Relevance
“…Reactivity studies revealed that the hydride has significant anionic character, undergoing protonolysis with mild acids like MeOH, and insertion with electrophiles like CO 2 and 3‐hexyne. More recently, Warren has demonstrated that reduction of a dicopper(II) hydroxide complex with Ph 3 SiH results in the ultimate formation of a bridging dicopper(I) dinitrogen complex . Strikingly, the authors were able to show that this reaction proceeded through a transient mixed‐valent copper(I)/copper(II) monohydride intermediate (Scheme , middle), which they were able to characterize by EPR spectroscopy and X‐ray diffraction studies.…”
Section: Methodsmentioning
confidence: 99%
“…Reactivity studies revealed that the hydride has significant anionic character, undergoing protonolysis with mild acids like MeOH, and insertion with electrophiles like CO 2 and 3‐hexyne. More recently, Warren has demonstrated that reduction of a dicopper(II) hydroxide complex with Ph 3 SiH results in the ultimate formation of a bridging dicopper(I) dinitrogen complex . Strikingly, the authors were able to show that this reaction proceeded through a transient mixed‐valent copper(I)/copper(II) monohydride intermediate (Scheme , middle), which they were able to characterize by EPR spectroscopy and X‐ray diffraction studies.…”
Section: Methodsmentioning
confidence: 99%
“…We note that the related dicopper dinitrogen complex [ iPr2 TpCu] 2 (-N 2 ) has been structurally and spectroscopically characterized with an N-N distance of 1.111(6) Å and (NN) = 2130 cm -1 pointing to a gently reduced N 2 ligand. 73 We modeled these redox tautomers 9a' -9d' by DFT as triplet species because in the prototypical case of 9c' (Figure 14b), the triplet configuration is 7 kcal/mol more stable than the unrestricted open-shell singlet 9c'-singlet (Table S3). Although these pyridinium radical/dinitrogen redox tautomers [ xHetH TpCu] 2 ( -N 2 ) (9a' -9d') are calculated to be 6.4 -20.2 kcal/mol higher in free energy at 298 K than the corresponding H-bonded diazene complexes [ xHet TpCu] 2 ( -N 2 H 2 ) (2a' -2d'), there is a clear trend in their relative stabilities (Figure 14c).…”
Section: Systematic Study Of H-bonding With N 2 H 2 By Ir Spectroscopymentioning
confidence: 99%
“…A dual-template (molecular imprinting template and mesoporous template) docking oriented molecular imprinting method for one-pot synthesis of mesoporous MIPs with recognition sites located on the surface of mesoporous silica was proposed. [202][203][204][205][206] As shown in Fig. 8C, rod-like positively charged CTAB micelles were mixed with negatively charged template to form dualtemplate complexes based on electrostatic attraction.…”
Section: Homogeneous Mesoporous Mipsmentioning
confidence: 99%
“…9E shows a TEM image of phosphate-imprinted mesoporous silica using the dual-template method, with mesopore diameter of 2.6 nm and specific surface area of 792 m 2 g À1 . 204 Similarly, Hu 205 prepared mesoporous MIPs to recognize phosphorylated tyrosine residue using this dual-template docking method. Template phenylphosphonic acid is negatively charged in alkaline solution, which can be docked onto CTAB micelles to form a dual-template due to electrostatic attraction.…”
Section: Homogeneous Mesoporous Mipsmentioning
confidence: 99%